MODEL CUPs BERBANTUAN PhET UNTUK MEREMEDIASI MISKONSEPSI GETARAN HARMONIS SMAN 1 SUNGAI RAYA - Ghalih Prasetyo; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2020)
Abstracthitung This study aimed to determine the effectiveness of the application of CUPS learning model assisted by PhET simulations to reduce the learners’ misconceptions on a harmonic osilation at SMAN 1 Sungai Raya. This study was conducted through an experimental study in the form of pre-experimental design by one group pre-test post- test design with a total sample of 23 students in class X MIA 4. The instrument used in this study was a diagnostic test which consists of 10 multiple-choice questions in the form of open ground. From the calculation of the result of pretest and posttest data, there was a reduction number of learners who had misconceptions (average∆S= 57.75%) after remediation with CUPS learning model assisted by PhET simulations. Based on the analysis using the McNemar test, there was a significant conceptual change occurred (32 = 15.27; df = 1; α = 5%) after remediation with CUPSlearning model assisted by PhET simulations. The application of CUPS learning model assisted by PhET simulations were effective in decreasing the learners’ misconceptions with high category (O = 6,75). This research hopefully can be used as an alternative way to reduce the number of learners’ misconceptions in learning activities.Keyword: Conceptual Understanding Procedures, Harmonic Oscillation, Misconceptions